Persisting multiple organ dysfunction syndrome in a patient with severe polytrauma: a case report - E. V. Grigoriev; S. V. Voevodin; A. V. Kovalenko; D. A. Rudakova (Фундаментальная и клиническая медицина, 2021)
Persistent multiple organ failure is a new phenotype of a critical patient capable of leveling all the initial successes in treating a patient in the intensive care unit, which is associated with an increase in the need for methods of organ function replacement, the development of cognitive deficits, muscle weakness and polyneuropathy of critical care. A case study is presented that demonstrates the effectiveness of primary resuscitation of a patient with severe polytrauma with further persistence of multiple organ failure and the need for long-term therapy aimed at recovering a critical patient and with an emphasis on drugs affecting cognitive function.